A location privacy protection algorithm based on differential privacy in sensor network. (13th January 2022) - Kou, Kaiqiang; Liu, Zhaobin; Ye, Hong; Li, Zhiyang; Liu, Weijiang
The continuous development and innovation in sensor networks has simplified the processes of data collection and transmission and has led to their widespread use. However, these processes often involve sensitive location information. Therefore, the location of a sensor should be protected for privacy reasons during data collection and transmission. In this paper, we propose a privacy protection scheme for location in a sensor network, based on differential privacy. Although the algorithm satisfies the privacy protection requirements, the accumulation of noise in the privacy protection process may decrease the utility of the data. To solve this problem, we propose a square sum error-based location privacy protection algorithm. Our algorithm can reduce the accumulation of noise, while also protecting the structure of the sensor network.